Հնդկաստանի Հանրապետության արտաքին քաղաքանությունը Հարավային Կովկասում հետխորհրդային շրջանում (1991-2011 թթ.) - Սահակյան, Գառնիկ («Զանգակ - 97»)
The main goal of the article is to study the transformation of the South Caucasus direction of the foreign policy of the Republic of India in the post-Soviet period, 1991-2011. The article separately discusses the course of bilateral relations between India-Armenia, India-Georgia, and India-Azerbaijan. Most of all India was interested in developing partnership with Azerbaijan because of its oil and gas reserves. The trade between the two states was greater than with Georgia and Armenia. One of the outcomes of the research is that India's policy in the South Caucasus was proceeding rather slowly, but steadily. India didn’t adopt a strategic policy towards the South Caucasus. The economic sphere received more priority. India’s strategy in the region became more conceptual and ambitious when the country transferred to the fifth largest economy in the world. The study’s methodology is based on discourse and content analysis․
Keywords: Հնդկաստան; Արտաքին քաղաքականություն